Shear Strengthening of RC Deep Beams with Symmetrically or Asymmetrically Positioned Square Openings Using CFRP Composites and Steel Protective Frames - Hamid Karimizadeh; Abolfazl Arabzadeh; Mohammad Reza Eftekhar; Asghar Amani Dashlejeh (Advances in Civil Engineering)
In most cases, openings are made in the Web of deep beams for installations to pass through. These members require to be strengthened since the openings reduce load-bearing capacity. This study utilizes carbon fiber-reinforced polymer (CFRP) composites and steel protective frames (SPF) as strengthening configurations in reinforced concrete (RC) deep beams to improve the strength lost due to the square openings. To this end, eleven specimens with 10 × 50 × 120 cm in size were subjected to the three-point monotonic loading. In each beam, one or two square openings of 18 cm in each side are positioned either symmetrically or asymmetrically along the beam before it is strengthened with CFRP composites or SPFs. The strengthening composites were installed using externally bonded reinforcement (EBR) or externally bonded reinforcement on grooves (EBROG) techniques in two wrapped or inclined configurations. The obtained results indicate that specimens retrofitted by the SPF exhibited a superior performance as their loading capacity and energy absorption were enhanced by 115% and 337% in comparison with the reference beam, respectively, while these values for the specimens retrofitted by the EBROG technique were 58% and 182%, respectively, and 42% and 105% for those strengthened with the EBR technique.